Evaluating the correlation between Emotional Intelligence (EI) and Effective Leadership (EL) among managers in Miri Shipbuilding Industry - Singh, Mitrabinda; Hii, Linda; Lum, G. (IACSIT Press, Singapore, 2012)
This article investigates the correlation between Emotional Intelligence (EI) and Effective Leadership (EL) among project managers. Miri shipbuilding industry is chosen for the study due to the reason that the project managers of the shipbuilding companies are facing many challenges from the market right from supply chain to distribution. To retain subordinates and make them work for the success of the projects is the biggest challenge for the project managers of Miri shipbuilding industry. This study is conducted to help the industry find the correct measures to resolve the issues mentioned. Two sets of questionnaires were distributed to the project managers and their subordinates to determine the EI factors that contribute to effectiveness of the leadership quality of the project managers. Data was collected from 8 companies. 50 managers and 8 project managers participated in this study. Many studies have been done in this area in different industries and significant correlation is found evident in many studies. Based on Goleman’s EI indicators to determine effectiveness of leadership, this study also shows significant results. Motivation, an indicator of EI shows significant correlation with the effectiveness of the leader. EI and EL also show significant correlation.